Mussel Fauna of the Powell River, Tennessee and Virginia - Sally D. Dennis (Hello World!, 1981)
A survey of the fresh water mussels of the Powell River conducted in 1973 through 1978 revealed a rich Cumberlandian mussel fauna inhabiting a sixty mile (96.5 km) reach of the river. Thirty-six species were found, five of which are designated endangered. Mussel densities at two selected sites were high, averaging six and twelve mussels per square meter. With improvement of siltation problems associated with mining activities, this river will present an excellent opportunity for perservation and expansion of this unique fauna.